Archaeological evidence of woody vines at Bubog 2, Ilin Island, Mindoro, Philippines. - Carlos, Jane B (Archīum Ateneo, 2018)
Ethnographic and historical records in the Philippines document the use of vines for cordage, mats, baskets, hats, medicine, and furniture. Similar usage has been assumed in the more distant past (i.e., neolithic); however, no material evidence has so far been found probably owing to unfavorable conditions inhibiting preservation of this particular organic material. This paper reports the presence of dried and mineralized fragments of woody vines from the archeological site of Bubog 2 in Ilin Island, Mindoro, Philippines. Identified as coming from the families Annonaceae, Dilleniaceae, and Mimosaceae, this occurrence provides the first archaeobotanical evidence in the Philippines of woody vines in layers dated from 5000 BCE to 1000 CE.